2021
DOI: 10.3390/nu13041206
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Lactoplantibacillus plantarum Strains CECT7527, CECT7528, and CECT7529 Plus Monacolin K Reduces Blood Cholesterol: Results from a Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Background: Dietary supplements have been proposed to help manage blood cholesterol, including red yeast rice (RYR) extracts, plant sterols and stanols, beta-glucans, and some probiotics. This study was conducted to evaluate the efficacy of RYR (containing 10 mg of monacolin K) combined with 109 CFU of three Lactoplantibacillus plantarum strains (CECT7527, CECT7528, and CECT7529). Methods: A 12-week randomized, double-blinded, placebo-controlled clinical trial was conducted. In total, 39 adult patients were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Consistent with animal experiments, probiotic supplementation also significantly reduces serum TC and LDL-C in patients with hyperlipidemia ( Sharma et al., 2016 ). A 12-week randomized, double-blind, placebo-controlled clinical trial has shown that the combination of three Lactobacillus plantarum strains can reduce blood cholesterol in patients ( Guerrero-Bonmatty et al., 2021 ). Additionally, a study involving 70 healthy adults has demonstrated that the daily supplementation of Lactobacillus plantarum Q180 can significantly improve blood-lipid indicators such as LDL-C and TC after meals by adjusting the composition of the intestinal flora ( Park et al., 2020 ).…”
Section: Treatment Of Hyperlipidemia Targeted At Gut Microbiotamentioning
confidence: 99%
“…Consistent with animal experiments, probiotic supplementation also significantly reduces serum TC and LDL-C in patients with hyperlipidemia ( Sharma et al., 2016 ). A 12-week randomized, double-blind, placebo-controlled clinical trial has shown that the combination of three Lactobacillus plantarum strains can reduce blood cholesterol in patients ( Guerrero-Bonmatty et al., 2021 ). Additionally, a study involving 70 healthy adults has demonstrated that the daily supplementation of Lactobacillus plantarum Q180 can significantly improve blood-lipid indicators such as LDL-C and TC after meals by adjusting the composition of the intestinal flora ( Park et al., 2020 ).…”
Section: Treatment Of Hyperlipidemia Targeted At Gut Microbiotamentioning
confidence: 99%
“…Therefore, the effect of probiotic dose levels on glycaemic control in patients with T2DM requires confirmation in other studies. Guerrero-Bonmatty et al showed that the combination of monacolin K (a statin) and L. plantarum strains was more effective in reducing LDL-C and TC levels in the treatment of hypercholesterolemia [ 76 ]. Therefore, in the future, some studies concerning probiotics in combination with statins, versus probiotics alone, could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Placebo capsule contained 440 mg maltodextrin, 0.5 mg silicon dioxide and 95 mg capsule shell (hydroxypropyl cellulose, dyed with titanium dioxide). Manufacturing procedures of the Lactobacillus preparation have been described elsewhere [17]. The sample size was n = 42 per group calculated based on a previous study with hypercholesteremic patients [13], estimating a moderate effect size of 0.3, a signi cance level of 5% (two-sided) at a power of 80%.…”
Section: Methodsmentioning
confidence: 99%